2018
DOI: 10.1210/js.2017-00447
|View full text |Cite
|
Sign up to set email alerts
|

Elevated (Pro)renin Receptor Expression Contributes to Maintaining Aerobic Metabolism in Growth Hormone Deficiency

Abstract: ContextGrowth hormone deficiency (GHD) leads to obesity and may induce tissue hypoxia. As (pro)renin receptor [(P)RR] is reported to contribute to the aerobic metabolism by stabilizing pyruvate dehydrogenase (PDH), it may play a substantial role in GHD.ObjectiveWe aimed to investigate serum soluble (P)RR [s(P)RR] concentration, the origin of s(P)RR, and significance of (P)RR in GHD.Design, Setting, and ParticipantsSerum s(P)RR concentration was examined in 72 patients with pituitary diseases, including 32 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Serum s(P)RR concentration showed completely different features compared with urinary s(P)RR excretion, and showed significantly positive relationships with age, BMI, WC, VFA, urine Alb excretion, Hb, uric acid, Cre, Ca, BS, insulin, HbA1c, TG, and hsCRP, and significantly negative relationships with urine pH, eGFR, and HDL-cholesterol (Table 4). These data are in accordance with those of previous investigations reporting that blood s(P)RR levels are associated with obesity [30], dyslipidemia [15], renal dysfunction [15,21], and inflammation [22]. These findings suggest that blood s(P)RR concentration is affected by the expression levels of tissue RAS and/or tissue (P)RR in various organs.…”
Section: Plos Onesupporting
confidence: 92%
“…Serum s(P)RR concentration showed completely different features compared with urinary s(P)RR excretion, and showed significantly positive relationships with age, BMI, WC, VFA, urine Alb excretion, Hb, uric acid, Cre, Ca, BS, insulin, HbA1c, TG, and hsCRP, and significantly negative relationships with urine pH, eGFR, and HDL-cholesterol (Table 4). These data are in accordance with those of previous investigations reporting that blood s(P)RR levels are associated with obesity [30], dyslipidemia [15], renal dysfunction [15,21], and inflammation [22]. These findings suggest that blood s(P)RR concentration is affected by the expression levels of tissue RAS and/or tissue (P)RR in various organs.…”
Section: Plos Onesupporting
confidence: 92%
“…Wu et al [ 19 ] reported that blood s(P)RR levels were high in a mouse model of diet-induced obesity. Furthermore, in humans, it has been reported that adult growth hormone deficient patients with visceral fat accumulation showed high blood s(P)RR levels and that these levels were related to BMI [ 25 ]. However, these reports did not sufficiently demonstrate whether obesity is associated with blood s(P)RR levels independently of other comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%